Aspectos do Comportamento Espaço-temporal de Programas Funcionais em Uni e Multiprocessadores - Souza, Francisco Vieira de; Lins, Rafael Dueire (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1998)
This paper analyses the performance of two of the most important techniques for automatic dynamic memory management in lazy functional languages. Our results show that, as garbage, collection enforces data locality, it is cheaper to garbage collect than to avoid it by increasing heap size. We observed this behaviour both in uni and multiprocessors running on operating systems with virtual memory.